2022
DOI: 10.3389/fimmu.2022.995432
|View full text |Cite
|
Sign up to set email alerts
|

Communication is key: Innate immune cells regulate host protection to helminths

Abstract: Parasitic helminth infections remain a significant global health issue and are responsible for devastating morbidity and economic hardships. During infection, helminths migrate through different host organs, which results in substantial tissue damage and the release of diverse effector molecules by both hematopoietic and non-hematopoietic cells. Thus, host protective responses to helminths must initiate mechanisms that help to promote worm clearance while simultaneously mitigating tissue injury. The specialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 197 publications
0
7
0
4
Order By: Relevance
“…The immune response against parasite helminths, where myeloid cells play essential roles in inducing protection in the host, has been described widely. Mast cells, basophils, dendritic cells, neutrophils, monocytes, and macrophages have prominent roles whereby IL-4/IL-13 polarizing cytokines participate in resolving the infection in favor of the host [ 20 ]. Basophils promote intestinal helminth clearance, inducing increased amounts of IL-4 and prostaglandins, favoring the antigen presentation to T-CD4 + cells, and promoting the development of M2 macrophages to repair the damaged tissues [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immune response against parasite helminths, where myeloid cells play essential roles in inducing protection in the host, has been described widely. Mast cells, basophils, dendritic cells, neutrophils, monocytes, and macrophages have prominent roles whereby IL-4/IL-13 polarizing cytokines participate in resolving the infection in favor of the host [ 20 ]. Basophils promote intestinal helminth clearance, inducing increased amounts of IL-4 and prostaglandins, favoring the antigen presentation to T-CD4 + cells, and promoting the development of M2 macrophages to repair the damaged tissues [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells, basophils, dendritic cells, neutrophils, monocytes, and macrophages have prominent roles whereby IL-4/IL-13 polarizing cytokines participate in resolving the infection in favor of the host [ 20 ]. Basophils promote intestinal helminth clearance, inducing increased amounts of IL-4 and prostaglandins, favoring the antigen presentation to T-CD4 + cells, and promoting the development of M2 macrophages to repair the damaged tissues [ 20 , 21 ]. Another source of IL-4, essential to generating M2 macrophages during helminth infections, is the T-CD4 + lymphocyte, where the synergy between T cells and group 2 innate lymphoid cells (ILC2) for IL-13 production has been described [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…MCs are known for their biological role in allergic reactions but are also now known to be involved in many other important physiological and pathological processes ( 27 , 28 ). MC infiltration has also been found in some human and animal tumor models; however, its function in the tumor microenvironment remains controversial ( 26 , 29 ). Further studies of the role of MCs in NSCLC are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Th1-type immune response gradually changes to the Th2-type immune response, which is contributed to survive for the worms in host. And some researchers [32,33] found that in the early stage of worm infection, anti-in ammatory factors showed an upward trend. Our research results also support this statement.…”
Section: Discussionmentioning
confidence: 99%